Kegiatan Khatam Qur’an di Koto Lipek Pageh Kabupaten Solok - Fitra, Halkadri; Sapta Jonesti, Abi; Saputra, Doni; Pathoroni, Hefri; Aulia Rahman, Faishal; Farhan, Ananda (Manaruko: Jurnal Pengabdian Masyarakat, 2025)
The Quran completion event held on February 25, 2025, in Koto Lipek Pageh, was a significant moment for the local community to show respect for the Quran and strengthen their faith. The event was attended by various groups, from children to adults, demonstrating high enthusiasm for this tradition. The series of activities included a collective recitation of the Quran, a prayer led by a local scholar, the distribution of aid to orphans, and a cultural performance featuring religious artistic expressions. This event aimed not only to enhance understanding and practice of Islamic teachings but also to strengthen social bonds among residents. Through the Quran completion, it is hoped that the community can become closer to the values of the Quran and apply them in daily life, while also establishing this activity as a sustainable tradition for future generations